A handbook of terrorism and insurgency in Southeast Asia - Tan, Andrew T. H. (Andrew Tian Huat); Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
This timely and significant book seeks to explain the deep-seated complexities of terrorism and insurgency in Southeast Asia. In the aftermath of 9/11, this region has been designated by the United States to be the 'second front' in the war on terrorism. Yet despite the emergence of this 'new' global terrorism, the authors argue that armed rebellion in Southeast Asia is a phenomenon that predates Al Qaeda and the global Jihadist movement and that much can be learned from the motivations behind it.
Terrorism in Southeast Asia -- Terrorism and insurgency in Southeast Asia / Andrew T H Tan -- Setting the post 9-11 context : the emergence of postmodern terrorism / Andrew T H Tan -- Old terrorism in Southeast Asia : a survey / Andrew T H Tan -- The challenge of radical islam -- Militant Java-based Islamist movements / Greg Fealy -- Jemaah Islamiyah according to PUPJI / Elena Pavlova -- Suicide terrorism and Southeast Asia / Adam Dolnik -- Human tragedy in Sulawesi, Indonesia : 1998-2002 / James Veitch. -- Jihad in Maluku / Badrus Sholeh -- Al-Maunah and KMM in Malaysia / Elina Noor -- 'Radical Muslim terrorism' in the Philippines / Rommel C. Banlaoi -- Armed separatist insurgencies -- Separatist insurgency in the southern Philippines / Paul A. Rodell -- The Aceh conflict : phases of conflict and hopes for peace / Kamarulzaman Askandar -- The Malay-Muslim insurgency in southern Thailand / Thitinan Pongsudhirak -- Separatism in Papua / Philips J. Vermonte -- Ethnic conflicts in Burma : from separatism to federalism / Martin Smith -- State terrorism -- State terrorism in Arakan / Syed Serajul Islam -- The Hmong rebellion in Laos : victims or terrorists? / Gary Yia Lee -- East Timor under Indonesian occupation, 1975-99 / Peter Carey -- Communist insurgency -- The communist insurgency in the Philippines / Miriam Coronel Ferrer -- Counter-terrorism -- Terrorism in Southeast Asia - threat and response / Rohan Gunaratna -- The triad of twenty-first century counter-terrorism / Renato Cruz De Castro.
Includes bibliographical references and index.
Keywords: Terrorism -- Southeast Asia; Terrorism -- Religious aspects -- Islam; Electronic books